2009
DOI: 10.1186/1756-6606-2-8
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan 2,3-dioxygenase is a key modulator of physiological neurogenesis and anxiety-related behavior in mice

Abstract: Although nutrients, including amino acids and their metabolites such as serotonin (5-HT), are strong modulators of anxiety-related behavior, the metabolic pathway(s) responsible for this physiological modulation is not fully understood. Regarding tryptophan (Trp), the initial ratelimiting enzymes for the kynurenine pathway of tryptophan metabolism are tryptophan 2,3-dioxygenase (TDO) and indoleamine 2,3-dioxygenase (IDO). Here, we generated mice deficient for tdo (Tdo -/-). Compared with wild-type littermates,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
276
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(292 citation statements)
references
References 51 publications
14
276
1
1
Order By: Relevance
“…These results confirm the effect of Tdo2 on decidualization. Because both inhibition and targeted disruption of Tdo2 could lead to an increase in available tryptophan and circulating serotonin levels (Salter et al 1995, Kanai et al 2009), Tdo2 expression in decidualized cells demonstrated that Tdo2 might increase tryptophan catabolism in the decidual zone and decrease available tryptophan for production of serotonin that could inhibit the process of decidualization (Mitchell et al 1983), which further supports a role for Tdo2 in decidualization. Tdo2 is a rate-limiting enzyme of the tryptophan degradation pathway, producing kynurenine (Thackray et al 2008).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…These results confirm the effect of Tdo2 on decidualization. Because both inhibition and targeted disruption of Tdo2 could lead to an increase in available tryptophan and circulating serotonin levels (Salter et al 1995, Kanai et al 2009), Tdo2 expression in decidualized cells demonstrated that Tdo2 might increase tryptophan catabolism in the decidual zone and decrease available tryptophan for production of serotonin that could inhibit the process of decidualization (Mitchell et al 1983), which further supports a role for Tdo2 in decidualization. Tdo2 is a rate-limiting enzyme of the tryptophan degradation pathway, producing kynurenine (Thackray et al 2008).…”
Section: Discussionmentioning
confidence: 80%
“…Tdo2-deficient mice displayed an elevation of plasma tryptophan, making more of this amino acid available for uptake into the brain, where it is converted to serotonin (Kanai et al 2009). Tdo2 has also been identified in skin, brain, epididymis, testis, and early concepti, although it was mainly expressed in the liver (Suzuki et al 2001, Minatogawa et al 2003, Britan et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…We did not observe obvious toxicity in mice treated with LM10 for 3 months. Moreover, mice genetically deficient for TDO2 were recently obtained and found viable and healthy (35). The main observation in those mice is a reduced anxiety, which may result from their highly increased serum levels of tryptophan.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that other metabolic fates of Trp in brain could also modulate behavior (reviewed in Ref. 39), most notably its conversion to the neuroactive metabolite kynurenic acid (KYNA) (30,34,36,39,81).…”
mentioning
confidence: 99%